Treating prolactinoma and psychosis: medication and cognitive behavioural therapy - Nieman, DH (BMJ Publishing Group, 2011)
The patient in this case report had two severe medical conditions that require oppositional treatment: prolactinoma and psychosis. A prolactinoma is a benign tumour of the pituitary gland that produces prolactin. Dopamine agonist medication is the first-line treatment in patients with prolactinoma. The psychotic symptoms started after a dosage increase of a dopamine D2-receptor agonist. Several antipsychotic medications were tried with and without the dopamine D2-receptor agonist, but severe command hallucinations remained. Cognitive behavioural therapy (CBT) was added which reduced the impact of the hallucinations to a great extent, indicating that CBT can have an additional positive effect in prolactinoma patients with psychosis that shows incomplete recovery after antipsychotic medication. Future research should be aimed at the severe and prolonged side effects of dopamine agonists in the treatment of prolactinoma patients with multiple risk factors for a psychotic decompensation.